(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2026)
Epilepsy is a chronic neurological disorder characterized by recurrent unprovoked seizures caused by abnormal electrical activity in the brain. It is one of the most common neurological disorders in children and significantly affects cognitive, behavioral, and developmental outcomes. Antiepileptic drugs (AEDs) remain the cornerstone of pediatric epilepsy management, requiring continuous evaluation of their efficacy, safety, and medication adherence. This prospective observational study evaluated the prescribing patterns, effectiveness, safety, and adherence to AED therapy among 100 pediatric epilepsy patients. Data were collected from hospital records, patient case files, and caregiver interviews, including demographic characteristics, seizure type, AED prescriptions, treatment duration, adverse drug reactions (ADRs), adherence, and clinical outcomes. The majority of patients were aged 1 month to 5 years (85%), with males accounting for 65% of cases. Generalized seizures were the most common presentation (92%), and levetiracetam (Levipil) was the most frequently prescribed AED (73%). High medication adherence was observed in 38% of patients, while 35% showed moderate and 27% low adherence. ADR assessment using the Uppsala causality scale classified 45% as probable, 42% as possible, and 13% as certain. According to the International League Against Epilepsy (ILAE) outcome classification, most patients were categorized as Class 2 (53.3%). The study concludes that AED therapy is generally effective and well tolerated, while improved medication adherence, early diagnosis, and appropriate drug selection are essential for optimizing clinical outcomes in pediatric epilepsy.